Application of artificial neural network for wind speed prediction - Johari, Juzaili 'Izzati (2012)
This paper presents the application of Artificial Neural Network (ANN) for predicting wind speed in Malaysia by using a historical of meteorological data. Wind energy depends on the wind speed, which is random variable. The artificial neural network was trained using error back propagation learning rule. Meteorological data measured during four years from Kuala Terengganu weather station were used to form learning patterns. The trained artificial neural network was tested with different patterns. As a result, the model based on the neural network showing that the predicted wind speed values are in good agreement with the actual wind speed values.